The Expectations and Effects of Tax Cuts: Scenario Examples - Funda Karakoyun (Maliye Çalışmaları Dergisi)
Various incentives are organized in different types of taxes to support the financial structures of enterprises. These incentives impact decisions for taxpayers planning taxes. The regulations that are included in legislation as tax deductions are seen as the perception and expectation of a decrease in taxpayers’ tax burden. The literature has discussed the positive impact of tax incentives on production, employment, and investment decisions and emphasized the importance of supporting taxpayers, especially in times of crisis. In terms of regulations with the purpose of providing incentives in legislation containing issues that are open to interpretationand discussion regarding the implementation results, this study takes tax deductions as the subject of examination. This study presents scenarios on how tax deductions reflect onto taxpayers in practice using two examples and calculates the change in tax liability caused by a reduction in the withholding tax rates for rental income and profit distribution. Accordingly, the study evaluates the difference between taxpayers’ expectations and the actual tax payment. Tax liability for property owners is seen to increase because of reducing the rent withholding tax rate. The tax burden is seen to not get reduced as a result of the dividend withholding tax deduction; however, an effect is seen to occur mainly related to tax deferral. Although the implementation results vary according to the taxable income brackets, to interpret the uniform tax burden as increasing or decreasing when rates change would be an incomplete assessment.